Erudición griega y romana en Schol. Veron. Aen. 3, 705: los límites de la atribución de fragmentos (Ordia Prima, 2024)
Abstract: Drawing on a poorly transmitted passage (Schol. Veron. Aen. 3, 705) that has been attributed to several Greek and Latin authors, this work reflects, in general, on the risks posed by the ascription of fragments transmitted by sources with textual difficulties, and reviews, in particular, the different proposals for the authorship of the passage in question. The excerpt discusses the forms taken by the demonyms of Greek toponyms –such as Selinus and Amathus– and contributes a piece of evidence about Olympic champions. This contribution tries to explain all this within the context, including a proposal for the reconstruction of the original text.
Keywords: fragments